REDES SOCIAIS INFORMAIS E ESPOSAS NA ATENAS DE ARISTÓFANES - Lessa, Fábio de Souza (PHOÎNIX, 2020)
This article's aim is to study the integration, in the classical period Athenian society, of the "well-to-do" wives into the informal social nets. A ristofanes' comedy "Lysistrata" will be the textual register used for this study.